ANALISIS KINERJA KADER TERHADAP PENEMUAN KASUS TUBERKULOSIS PARU DI UPTD PUSKESMAS BUMI AGUNG KOTA PAGAR ALAM TAHUN 2026 - Metty Hernita Padma Kencana; Ali Harokan; Nurul Fitriah (Universitas Pahlawan Tuanku Tambusai, 2026)
Pulmonary tuberculosis (TB) remains a major public health challenge in Indonesia. UPTD Puskesmas Bumi Agung recorded an average Case Detection Rate (CDR) of only 10.6% during 2023–2025, well below the national target of 90%. This research aims to analyze factors associated with the performance of health cadres in the detection of pulmonary TB cases. A quantitative analytical study with a cross-sectional design involving 239 health cadres (total sampling). Data were analyzed using univariate, bivariate (chi-square), and multivariate (multiple logistic regression) analysis. The majority of cadres (67.8%) had low TB case detection. Bivariate analysis showed significant associations with knowledge (p=0.022; OR=2.125), training (p<0.001; OR=7.667), healthcare worker support (p<0.001; OR=3.418), cadre activeness (p<0.001; OR=8.522), workload (p=0.030; OR=3.641), and experience (p<0.001; OR=30.104). Multivariate analysis identified three dominant variables: cadre experience (OR=21.781), workload (OR=8.744), and activeness (OR=2.710). The model explained 60.2% of case detection variation. Cadre experience is the most dominant factor. Capacity building through periodic training, mentoring programs, and workload redistribution are essential to improve pulmonary TB case detection.